Difficulties and challengesof school physical education teachers in pandemic times (Citizenship in Action: Extension and Culture Magazine, 2023)
The year 2020 was undoubtedly quite troubled with the emergence of the COVID-19 pandemic, affecting the entire planet. With the rapid spread of the virus, several health measures had to be adopted, especially social distancing, several areas of society were affected, such as the economy and education. One measure adopted by the government was the closure of schools, relocating classes to the format of remote classes. In the present, the objective was to answer the question: How was the process of construction of learning and evaluation of School Physical Education classes of the Public and Private Network of Lucas do Rio Verde - MT developed during the COVID-19 pandemic from the perceptions of the students? School Physical Education teachers? Through the diagnostic survey contained in the reports of Mandatory Supervised Internships Initial Years, carried out in 2020-1, it was possible to reach the following conclusions: the new forms of teaching resulting from the pandemic, using technologies, remote and hybrid classes is a viable way, but which must be discussed and analyzed, given the difficulties of students and teachers; planning was extremely affected, since most of the "practical" classes cannot be carried out effectively. The evaluation was hampered as the school body and students were not prepared to face the challenges that the pandemic and remote classes presented.
Keywords: learning; remote classes; covid 19 pandemic; physical education